Health care utilizationand cost among the elderly in Miag-ao, Iloilo. - Evaristo, Herlie Rubite...[et. al.]. (Miag-ao, Iloilo University of the Philippines Visayas, College of Arts and Sciences, Division of Social Sciences, 2008)
This paper described the health care utilization pattern and cost determined the significant factors affecting the utilization of health care services. The major illnesses mentioned were cough, headache, fever, influenza, arthritis, back pain, stomachache, high blood pressure, asthma and gastritis. The facilities frequently visited by those who sought medical care were the Rural Health Unit (RHU), private clinicss and private hospitals. More than the majority of the participants were attented by private doctors in private hospitals and clinics. Results of the Logistics Regression showed that the significant factors affecting the leder's health care utilization include the monetary costs incurred during consultation or hospitalization and if they have adult children who live with them. Higher monetary costs during consultation or hospitalization and presence of adult children both decrease the likehood of elders to seek professional care. Increasing the number of health care providers would lessen the time costs by reducing the waiting time before actual consultation. It is recommended that more studies on the elderly population and their health concerns be conducted as it is among those vulnerable populations that are given less attention on health care needs. Moreover, future similar studies should have a greater number of participants to increase the variability of responses and make the results more representative of the entire population.
Thesis - Undergraduate (Bachelor of Science in Economics)- University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Health care services